COMPARISON OF THE CONCEPT OF LEGAL CERTAINITY IN THE REGULATION OF THE DEATH IN THE OLD CRIMINAL CODE AND THE NATIONAL CRIMINAL CODE (INDONESIA) - Tantoi, Lalu Alex; Madjid, Abdul; Istiqomah, Milda (International Journal of Business, Law, and Education, 2023)
The presence of the death penalty in the new National Criminal Code (KUHP) enacted in 2023 has sparked a great deal of controversy. Just like its existence, the death penalty still generates many problems and has both proponents and opponents. This research employs a juridical-normative approach and utilizes methods of legal analysis, conceptual analysis, and comparison. The results reveal that the regulation of the death penalty is more legally uncertain when compared to the previous Criminal Code because it is considered highly open to multiple interpretations, lacks clarity, conflicts with other regulations, and presents numerous loopholes that can be exploited by irresponsible individuals for legal transactions.